Construction and Biological Characteristics of a Quadruple Gene-Deleted Strain of Orf Virus as a Vaccine Candidate - Jiawen Zhang; Ruolan Xin; Junjie Zhao; Ruizhi Wu; Daoming Su; Menglin Li; Yuanyuan Zhu; Xiaoyun Chen; Zhen Zhu (Viruses)
(1) Background: Contagious ecthyma, also known as orf, is an epitheliotropic zoonotic disease caused by the orf virus (ORFV), primarily affecting the skin and mucous membranes of ruminants such as goats and sheep, leading to the formation of papules and pustules. Vaccination is the most effective way to prevent this disease in susceptible animals; however, traditional attenuated vaccines carry the potential risk of reversion to virulence. Therefore, there is an urgent need to develop safe and effective vaccines for the prevention and control of orf. (2) Methods: In this study, building upon the previously constructed ORFV three-gene deletion strain rGS14-TrypMut, we employed homologous recombination to knock out the VIL-10 gene and successfully constructed a four-gene deletion strain, rGS14-QuadMut. We evaluated its in vitro growth characteristics, safety, and protective efficacy in a challenge model. (3) Results: The in vitro results show that rGS14-QuadMut had a replication ability similar to that of other two-gene deletion strains, with good genetic stability. In in vivo experiments, compared to rGS14-TrypMut, rGS14-QuadMut caused only mild redness and swelling at the inoculation site, with a faster healing rate, indicating better safety. Additionally, rGS14-QuadMut induced strong differentiation of CD4+ and CD8+ T cells, increased the CD4+/CD8+ ratio, and primarily stimulated a Th1-type immune response, with significant changes in cytokine levels, including IL-8, IFN-γ, and IL-2. In the challenge protection experiment, both rGS14-QuadMut and rGS14-TrypMut provided 100% protective efficacy. In conclusion, rGS14-QuadMut demonstrated enhanced safety without compromising immune protection efficacy and is a promising candidate for an orf live vaccine strain.